Impact of surface treatments on the corrosion resistance of ASTM F138-F139 stainless steel for biomedical applications - Pereda, M. D. (2012)
AISI 316 LVM stainless steel type considered in ASTM F138 and F139 standards for implant devices is widely used, in particular for orthopedic surgery, because it combines good biofunctionality and acceptable biocompatibility at low costs. Adequate interaction of these materials with the human body and its capability to reach the desired service level are determined by the surface preparation. The goal of the present work is to relate the surface roughness parameters with the localized corrosion resistance of AISI 316 LVM stainless steel grit blasted for different times and passivated with nitric acid. At intermediate blasting times the roughness parameters attain an extreme value and this surface condition corresponds with the maximum pitting corrosion resistance.